2011
DOI: 10.1177/0363546511405147
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Anterior Cruciate Ligament Injury in World Cup Alpine Skiing

Abstract: Based on this video analysis of 20 injury situations, the main mechanism of anterior cruciate ligament injury in World Cup alpine skiing appeared to be a slip-catch situation where the outer ski catches the inside edge, forcing the outer knee into internal rotation and valgus. A similar loading pattern was observed for the dynamic snowplow. Injury prevention efforts should focus on the slip-catch mechanism and the dynamic snowplow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
172
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 48 publications
8
172
0
5
Order By: Relevance
“…All age groups must compete in technical and speed disciplines; however, older athletes race more downhill and Super G. Previous studies have shown that the injury risk increased with event speed and was greatest in downhill events 16 27. In this study, there were fewer ACL injuries within the 18-year-old male and female racers.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…All age groups must compete in technical and speed disciplines; however, older athletes race more downhill and Super G. Previous studies have shown that the injury risk increased with event speed and was greatest in downhill events 16 27. In this study, there were fewer ACL injuries within the 18-year-old male and female racers.…”
Section: Discussionmentioning
confidence: 46%
“…In alpine skiing, the boot-induced anterior drawer mechanism is well known as one of the main causes of ACL ruptures 28. A recent study from Bere et al ,27 who investigated the mechanism of ACL injuries in World Cup alpine skiers, showed that the slip-catch situation is the main mechanism of ACL injuries. However, internal risk factors need to be identified as well.…”
Section: Discussionmentioning
confidence: 99%
“…The injury often occurs as a combination of compressive loading and twisting of the knee 19. This mechanism is typical in the alpine skiing discipline, when the skier loses balance or the ski edge catches during a turn 20 21. Upper limb and head injuries are often associated with falling from a jump 22 23.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we described the mechanisms of ACL injury based on systematic analyses of videos from 20 injury cases 5. This was the first study to describe the mechanisms of ACL injuries among professional ski racers (WC alpine skiers), and three distinctive mechanisms were identified and termed “the slip-catch”, “landing back-weighted” and “the dynamic snowplow”.…”
Section: Introductionmentioning
confidence: 99%